2022
DOI: 10.1186/s12966-022-01261-9
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of physical activity interventions using activity trackers during or after inpatient care: a systematic review and meta-analysis of randomized controlled trials

Abstract: Background Promoting physical activity (PA) in patients during and/or after an inpatient stay appears important but challenging. Interventions using activity trackers seem promising to increase PA and enhance recovery of physical functioning. Objective To review the effectiveness of physical activity interventions using activity trackers on improving PA and physical functioning, compared to usual care in patients during and/or after inpatient care.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 64 publications
0
13
0
1
Order By: Relevance
“…9 Previous studies evaluating the effect of interventions using activity trackers mainly focused on the minimal clinically important change of step counts in patients with a chronic disease. 16,17 Only few studies evaluated interventions with an activity tracker during hospital stay, whereby step count significantly increased. 28,29 Another study evaluated a smartphone application with an activity tracker in hospitalized patients on standing and walking time.…”
Section: Discussionmentioning
confidence: 99%
“…9 Previous studies evaluating the effect of interventions using activity trackers mainly focused on the minimal clinically important change of step counts in patients with a chronic disease. 16,17 Only few studies evaluated interventions with an activity tracker during hospital stay, whereby step count significantly increased. 28,29 Another study evaluated a smartphone application with an activity tracker in hospitalized patients on standing and walking time.…”
Section: Discussionmentioning
confidence: 99%
“…25 Goal setting is stated to be effective in improving physical activity in both hospitalized and nonhospitalized populations. 11 A previous review stated that the use of a movement sensor with a step goal is associated with a significant increase in physical activity. 26 In our study, patients received a movement sensor with a predefined movement goal based on preimplementation measurements of activity levels.…”
Section: Discussionmentioning
confidence: 99%
“…10 Interventions using movement sensors during or after an inpatient period have the potential to increase the level of physical activity across a wide range of surgical and nonsurgical populations on nursing wards. 11 Previous research looked into barriers and facilitators of patients' physical activity, from patients' and healthcare professionals' perspective. 12,13 They suggested that physical activity is influenced by patients' knowledge, awareness and attitudes.…”
Section: Introductionmentioning
confidence: 99%
“…Die Ergebnisse von de Leeuwerk et al 2 müssen aufgrund der hohen Heterogenität der Studien mit Vorsicht interpretiert werden. Die Übersichtsarbeit deckt eine breite Population von Patient*innen ab, es kann jedoch aufgrund der heterogenen Studien kein spezifischer Schluss oder keine Handlungsempfehlung zur Dauer oder Intensität der Intervention gemacht werden.…”
Section: Zusammenfassungunclassified